Proceedings of 2010 IEEE International Symposium on Circuits and Systems 2010
DOI: 10.1109/iscas.2010.5537493
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of logic gates and reconfigurability of neuromorphic switching networks

Abstract: Nanoparticle networks with functional molecular links that show current-voltage characteristics (IVC) with negative differential resistance (NDR) can be trained to perform XOR-AND logic gates (Husband et al.[1]; Sköldberg and Wendin [2]). In this work we investigate the robustness of the Nanocell network by removing links until desired logic gates no longer can be configured or operated within our simulation of the network. We present results for the robustness of XOR-AND configured (halfadder) Nanocells, as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The goal of early experimental investigations of NPSANs [7] was to build NP-networks linked by molecules showing negative differential resistance (NDR). Theoretical studies demonstrated how to configure logic gates in such networks complemented by output latches [8][9][10][11][12], but so far it has not been possible to produce molecular NDR links with useful characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The goal of early experimental investigations of NPSANs [7] was to build NP-networks linked by molecules showing negative differential resistance (NDR). Theoretical studies demonstrated how to configure logic gates in such networks complemented by output latches [8][9][10][11][12], but so far it has not been possible to produce molecular NDR links with useful characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…In 1999, Chen et al [34] published an experimental paper reporting strong effects of negative differential resistance (NDR) in a molecular junction. This formed the basis for a number of theoretical papers using a network of NDR molecules (Nanocell) for implementing logic gates, with the particular advantage of producing XOR gates [35][36][37][38][39][40]. Unfortunately the original NDR result could not be reproduced, and strong molecular NDR effects have turned out to be difficult to produce, and so far Nanocell logic remains a theoretical issue.…”
Section: Ndr Devices and Networkmentioning
confidence: 99%
“…The second approach, which our research group follows, consists of passive networks of interconnected memristors without neurons or active elements. These types of networks have been implemented using functional molecular links able to perform logic computations [2,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%